Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi Pada Perusahaan Food And Beverages Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021-2023 - Tri Enjelika Thennesius; Lambok D.R. Tampubolon (LPPM Universitas Buddhi Dharma, 2025)
This research is motivated by the Indofood CBP Sukses Makmur Tbk (ICBP) Company which experienced a significant increase in profitability during the first semester of 2023, where net profit was IDR 5.72 trillion with an increase of 196.6%, net sales were recorded at IDR 34.47 trillion with an increase of 5.28% and gross profit reached IDR 12.53 trillion with an increase of 20.46%, but ICBP's share price remained stagnant. This study aims to find out the effect of Profitability and Company Size on Company Value with Dividend Policy as a moderating variable. This study takes data from financial reports and annual reports of food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2021-2023. This study uses quantitative methods and data analysis techniques used, namely multiple linear regression . The determination of the sample in this study uses a purposive sampling technique. with a total sample in this study of 75 data from 25 companies. The results of this study are (1) Profitability has a positive and insignificant effect on Company Value, ( 2) Company Size has a positive and significant effect on Company Value, ( 3) Dividend policy cannot strengthen the relationship between profitability and company value, (4) Dividend policy has an effect but weakens the relationship between company size and company value. This study presents information about variables that can influence company value.